A systematic literature review of burden of illness in adults with uncontrolled moderate/severe asthma. (January 2022) - Czira, Alexandrosz; Turner, Monica; Martin, Amber; Hinds, David; Birch, Helen; Gardiner, Frances; Zhang, Shiyuan
Abstract: Background: There are limited published data on the burden of moderate/severe uncontrolled asthma. Methods: We conducted a systematic literature review to better understand the impact of moderate-to-severe asthma in the US, the UK, Germany, France, Italy, Spain, Canada, Japan, and Australia in terms of prevalence, clinical measures, health-related quality of life (HRQoL) and economic burden, for patients whose asthma is uncontrolled despite inhaled corticosteroid/long-acting β2 -agonist (ICS/LABA) therapy. Results: The prevalence of uncontrolled asthma among patients with moderate/severe disease varied but was as high as 100% in some subgroups. Patients with uncontrolled asthma generally had poor lung function (mean/median pre-bronchodilator forced expiratory volume in 1 second [FEV1 ]: 1.69–2.45 L; mean/median pre-bronchodilator percent predicted FEV1 : 57.2–79.7). There was also a substantial but variable exacerbation burden associated with uncontrolled asthma, with the annualised rate of exacerbations ranging from 1.30 to 7.30 when considering various patient subgroups. Furthermore, the annualised rate of severe exacerbations ranged from 1.66 to 3.60. The HRQoL burden measured using disease-specific and generic instruments consistently demonstrated substantial impairment of HRQoL for those with uncontrolled asthma; Asthma Quality of Life Questionnaire scores ranged from 3.00 to 5.20, whilst EurQol-5 Dimensions index scores ranged from 0.53 to 0.59. Direct, indirect and total costs together with consumption of other healthcare resources associated with managing uncontrolled asthma were also substantial in the population studied; no caregiver burden was identified. Conclusions: Our findings suggest that significant unmet needs exist for patients with uncontrolled asthma despite the availability of ICS/LABA therapy. Novel treatments are needed to help reduce the burden to patients, healthcare systems and society. Highlights: Poor asthma control, lung function and frequent exacerbations were common. Health-related quality of life was consistently impaired. Direct, indirect and total costs and health-resource utilisation were substantial. Significant unmet needs for better treatments still exist for such patients.